Confocal three-dimensional micro X-ray fluorescence based on synchrotron radiation for mineral analysis. Issue 10 (26th November 2017) - Jiang, Bowen; Zhu, Yu; Sun, Tianxi; Liu, Zhiguo; Li, Fangzuo; Sun, Xuepeng; Wang, Yabing; Ding, Kuke
ABSTRACT: The confocal three-dimensional micro X-ray fluorescence using polycapillary optics and a synchrotron radiation was applied to nondestructively analyze elemental compositions of minerals, and thereby obtain the three-dimensional distributions of elements in the minerals. Such confocal micro X-ray fluorescence had potential applications in the mineral prospecting, identification of jades, differentiation of stones.